Ectopic Intratracheal Thyroid: A Rare Cause of Airway Obstruction - Waheed Rahman; Nafil Ishaq Arimbrathodi; Faisal Abdulkader; Hussain Al-Enazi; Zeynel A. Dogan (Case Reports in Otolaryngology)
Ectopic intratracheal thyroid tissue (EITT) is a rare abnormality with only limited cases reported so far. The presenting symptoms can be very similar to those of bronchial asthma. We discuss the case of a 29-year-old man with subglottic ectopic thyroid, with a history of thyroid surgery for goiter, which has been managed with laser-assisted endoscopic approach. We have also included presenting symptoms, pathophysiology, diagnosis, and management of EITT. We aim to include EITT in the differentials of airway obstruction, particularly in those patients who have goiter or previous thyroid surgeries.